Patterns of Corporate Punishment in Corruption Crimes in the Indonesian Legal System - Mahmud, Ade; Ali Firman Z, Chepi; Syawali, Husni; ., Wildan; ., Sarah (KnE Social Sciences, 2023)
The issue of criminalizing corruption crimes involving corporations has become a concern because, recently, the phenomenon of corruption in several cases has involved corporations that are not easily subject to criminal sanctions. This research aims to analyze the criminal liability for corporations as perpetrators of corruption crimes in the Indonesian legal system and the pattern of punishment for corporations that commit corruption crimes. This research method applies the normative juridical method with a qualitative analysis of secondary data. The results show that law enforcement officials who determine corporations as suspects in corruption crimes and punish them but have difficulty in ensnaring corporations. One of the causes is the incomplete provisions regarding corporations as legal subjects in the anticorruption law. In addition, investigators have difficulty finding evidence and determining the identity of corporate offenders. The pattern of punishment for corporations is to apply a cumulative-alternative punishment pattern aimed at the corporation and its management. For corporations, the type of punishment imposed is fines or economic punishment aimed at recovering losses due to corruption or administrative punishment such as revocation of business licenses, while for the management, the punishment imposed is imprisonment and fines. Keywords: sentencing, corruption, corporation